Analysis of the relation between elevated neutrophil lymphocyte ratio, and erythrocyte sedimentation rate in Helicobacter pylori positive chronic gastritis patients - V., Priyadharshini; Dhande, Sachin K.; Hanumanram, Gowtham; G. S., Sanjay Surya; A., Gowri Shankar (International Journal of Advances in Medicine, 2022)
Background: Aim of the study was to analyse the relation between elevated neutrophil lymphocyte ratio (NLR), and erythrocyte sedimentation rate (ESR) in Helicobacter pylori (H. pylori) positive chronic gastritis patients, as compared to the control group containing H. pylori negative chronic gastritis patients. Methods: Chronic gastritis patients were segregated in equal numbers based on H. pylori status. NLR was calculated, and ESR noted from the observations, comparison was done between the control and the study groups. Results: A total of 100 patients were included in the study. The 50 each from the control and study group. An observation of elevation in NLR and ESR in H. pylori positive chronic gastritis patients, as compared to the control group was seen. With an average NLR of 2.43 and 1.43, in the control and study group, respectively. Conclusions: Raise in NLR in H. pylori positive chronic gastritis patients with an associated raise in ESR suggests, the severity of the infection and the need for eradication and prevent complications.